2016
DOI: 10.1080/09638237.2016.1207222
|View full text |Cite
|
Sign up to set email alerts
|

Aggression in psychiatric hospitalizations: a qualitative study of patient and provider perspectives

Abstract: Aggression is perceived to have a wide range of origins spanning personal experiences and organizational policies, suggesting that a wide range of prevention strategies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 30 publications
3
54
0
Order By: Relevance
“…() studies show that patient characteristics such as symptoms (including drug or alcohol use), personality traits and demographic factors can give rise to aggressive/violent behaviour. However, results from this review suggest that patients did not emphasize symptoms of mental illness as significant for their aggressive/violent behaviour, which is consistent with results from other qualitative studies (Ilkiw‐Lavalle & Grenyer, ; Lamanna et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…() studies show that patient characteristics such as symptoms (including drug or alcohol use), personality traits and demographic factors can give rise to aggressive/violent behaviour. However, results from this review suggest that patients did not emphasize symptoms of mental illness as significant for their aggressive/violent behaviour, which is consistent with results from other qualitative studies (Ilkiw‐Lavalle & Grenyer, ; Lamanna et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, several people indicated that the app helped with boredom or getting through the day during their involuntary stay at the hospital. This is consistent with other findings that the treatment environment is a major contributor to aggression, especially when there is a lack of activity or variation in activity [ 42 , 43 ]. We know from the literature that periods of inactivity and boredom are consistent with an increased likelihood of aggression and violence [ 43 ]; therefore, this study reinforces the idea that interventions that alleviate boredom could conceivably be used to reduce aggression in future research, as in the following cases:…”
Section: Resultssupporting
confidence: 93%
“…Twenty-seven studies explored violent and aggressive incident experiences in staff,81–96 patients,97–99 mixed groups100–106 and patient family members 27. Five studies explored the risk factors associated with verbal and physical aggression 35 37 107–109. Three studies explored mental health nurses’ perspectives on the response to violent situations in high secure environments: one on the psychological impact of physical assault on staff,110 one on making violence risk assessments in imminent violent situations111 and one on the decline of incident reports 112.…”
Section: Resultsmentioning
confidence: 99%